ATM Secure and Privacy Preservation System Using Random Pseudo Code Algorithm (International Journal of Scientific Research in Science and Technology, 2024)
The ATM Privacy Security System ensures the utmost security and confidentiality of users' financial and personal information during ATM transactions through a range of robust measures. These include encryption, continuous monitoring, and rigorous authentication protocols. By implementing such strategies, the system aims to thwart fraudulent attempts and unauthorized access, safeguarding users' sensitive data. Tailored specifically to counter unauthorized access and potential ATM theft, this comprehensive security system employs various protective measures. Prior to cash withdrawal, users receive an authorization acceptance message via a link sent to their registered phone number. Only the registered owner can proceed with the transaction, ensuring enhanced security and control. Furthermore, the system incorporates a unique verification method and actively monitors the number of individuals within the ATM room. An overcrowding control warning system alerts users with a sound when the occupancy exceeds one person, ensuring a secure environment for transactions. In addition to these features, the system is equipped with a vibration sensor to detect any suspicious activities within the ATM machine. In the event of potential theft, the sensor triggers an immediate alert to the nearby station for swift intervention. Overall, the ATM Privacy Security System offers the highest level of security for both ATM users and bank management. Its comprehensive features and proactive measures provide peace of mind and confidence in the safety of financial transactions.
Keywords: ATM privacy; Security System; Confidentiality; Financial Information; Encryption